Contextual Action Theory in Career Counselling: Some Misunderstood Issues - Valach, Ladislav (Canadian Journal of Counselling and Psychotherapy, 2007)
Current discussion of action theory is premised on the fact that many counselors may avoid action approaches because of previous misunderstandings. Article addresses 12 misunderstandings. Overall, action theory is presented as highly suitable for understanding human behavior and for counseling as it is based on a wide spectrum of research as well as using a language close to human experience.